Measurement of the top quark mass using single top quark events in proton-proton collisions at root s=8 TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; Fruehwirth,R; et al. (European Physical Journal C: Particles and Fields, 2017)
A measurement of the top quark mass is reportedin events containing a single top quark produced via the elec-troweaktchannel. The analysis is performed using data fromproton-proton collisions collected with the CMS detector atthe LHC at a centre-of-mass energy of 8 TeV, correspondingto an integrated luminosity of 19.7 fb−1. Top quark candi-dates are reconstructed from their decay to a W boson and a bquark, with the W boson decaying leptonically to a muon anda neutrino. The final state signature and kinematic propertiesof single top quark events in thetchannel are used to enhancethe purity of the sample, suppressing the contribution fromtop quark pair production. A fit to the invariant mass distribu-tion of reconstructed top quark candidates yields a value ofthe top quark mass of 172.95±0.77 (stat)+0.97−0.93(syst) GeV.This result is in agreement with the current world average,and represents the first measurement of the top quark massin event topologies not dominated by top quark pair produc-tion, therefore contributing to future averages with partiallyuncorrelated systematic uncertainties and a largely uncorre-lated statistical uncertainty.